A Review on Halal Medical Tourism - Mimma Maripatul Uula; Ihsanul Ikhwan (Halal Tourism and Pilgrimage, 2022)
This study aims to see the development of research "Halal Medical Tourismâ€ around the world published by journals with that theme. This study used a qualitative method with a blibliometric analysis approach. The data used is secondary data with the theme "Halal Medical Tourismâ€ which comes from the Scopus database of 101 published journals. Then, the data is processed and analyzed using the VosViewer application with the aim of knowing the research development blibliometric map "Halal Medical Tourism" in this world. The results of the study found that countries that contributed a lot to research "Halal Medical Tourism" are Malaysia, Indonesia, the United States, South Korea, Australia and China. Furthermore, based on the bibliometric keyword mapping, there are 4 clusters that are research lines namely: Development of halal medical tourism, Halal compliance in halal medical tourism, Halal medical tourism destinations and Halal medical tourism services. The most used words are tourism, service, medical tourism, hospital, destination, attitude, product, and Muslim tourist.